2016
DOI: 10.1002/arp.1533
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Integrated Geophysics and Geotechnics as a Paleolandscape Reconstruction Tool: Archaeological Prospection of (Prehistoric) Sites Buried Deeply below the Scheldt Polders (NW Belgium)

Abstract: During extensive construction works in Antwerp harbour, well preserved Late Glacial dune formations were discovered buried deeply below the Scheldt polders and covered by peat, organic matter (OM) rich clays and marine clayey to sandy sediments. First, coring based archaeological prospection strategies for evaluating prehistoric occupation levels in wetland landscapes are reviewed. Next, a more effective approach including near surface geophysical and geotechnical techniques is proposed and tested in Doelpolde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Human remains dating to the prehistoric periods (Mesolithic and Neolithic) were almost exclusively found in Wallonia thanks to excellent preservation conditions of caves and rock shelters. These contexts are absent in Flanders, where open-air burial sites were more likely to be destroyed or buried under meters of sediment, as often happens in dynamic alluvial and marine systems (Verhegge et al 2014(Verhegge et al , 2016Verhegge 2015;Sergant et al 2016).…”
Section: Biases Of the Data And Adopted Solutionsmentioning
confidence: 99%
“…Human remains dating to the prehistoric periods (Mesolithic and Neolithic) were almost exclusively found in Wallonia thanks to excellent preservation conditions of caves and rock shelters. These contexts are absent in Flanders, where open-air burial sites were more likely to be destroyed or buried under meters of sediment, as often happens in dynamic alluvial and marine systems (Verhegge et al 2014(Verhegge et al , 2016Verhegge 2015;Sergant et al 2016).…”
Section: Biases Of the Data And Adopted Solutionsmentioning
confidence: 99%
“…A combination of deductive and inductive approaches ( Table 4 ) might improve the performance of the model. Usually, there is an approximation of the palaeo-surface with an deductive approach, which is subsequently supported by a dense dataset of archaeological or geoscientific ground-truth data [ 17 , 52 , 13 ]. Zwertvaegher et al [ 17 ] developed an integrative process model to challenge the complexity of landscape evolution by combining a deductive approach to obtain a purged base layer and an inductive approach for the predictive modelling of archaeological finds within the landscape.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been several approaches to reconstruct pre-modern terrain based on the interpolation of large datasets from drillings, archaeological excavations, and outcrops [ 9 , 10 ]. Other studies combine archaeological excavation data and geophysical data to interpolate detected pre-modern surface heights [ 11 13 ]. Both approaches are inductive methods based on field data interpolation and elaborate (geo-)archaeological and geophysical fieldwork, and post-processing.…”
Section: Introductionmentioning
confidence: 99%
“…2) (Delefortrie et al, 2014). Previous studies have shown the suitability of the EMI method for the detection of peat excavation in polder areas (e.g., De Smedt et al, 2013;Verhegge, Missiaen, & Crombé, 2016). For the measurements at Raversijde, a Dualem-21S sensor was used with three different coil sizes (depth penetration of the different coils, respectively, 0.5, 1, and 3 m).…”
Section: Additional Ground-truth Data (Cores Cpt Emi)mentioning
confidence: 99%